1985
DOI: 10.1126/science.227.4682.57
|View full text |Cite
|
Sign up to set email alerts
|

Deepest Known Plant Life Discovered on an Uncharted Seamount

Abstract: The discovery of abundant autotrophic macrophytes living below 200 meters indicates their importance to primary productivity, food webs, sedimentary processes, and as reef builders in clear oceanic waters. Estimates concerning minimum light levels for macroalgal photosynthesis and macrophytic contributions to the biology and geology of tropical insular and continental borderlands must now be revised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
136
0
4

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(144 citation statements)
references
References 10 publications
4
136
0
4
Order By: Relevance
“…The deepest known alga is a rhodolith-forming coralline red algal species discovered on an uncharted seamount at 268 m depth in the Bahamas (Littler et al 1985). Little is known about the diversity of non-geniculate coralline red algae from Brazil deep water (Amado-Filho et al 2007;Villas-Boas et al 2009) in general and of rhodolith-forming species in particular.…”
Section: Introductionmentioning
confidence: 99%
“…The deepest known alga is a rhodolith-forming coralline red algal species discovered on an uncharted seamount at 268 m depth in the Bahamas (Littler et al 1985). Little is known about the diversity of non-geniculate coralline red algae from Brazil deep water (Amado-Filho et al 2007;Villas-Boas et al 2009) in general and of rhodolith-forming species in particular.…”
Section: Introductionmentioning
confidence: 99%
“…In the tropical western Atlantic (inclusive of Florida, the Bahamas, Jamaica, and Bermuda), only a handful of other submersiblebased studies have been conducted in reef environments in water greater than 50 m depth: these include the results of Lang (1974), Huston (1985), and Fricke and Meischner (1985) from Florida; Lang et al (1975) and Liddell and Olhurst (1988) from Jamaica; Littler et al (1985Littler et al ( , 1986, Blair and Norris (1988), Liddell et al (1997), and Norris and Olsen (1991) from the Bahamas; and Ballantine (1990) from Puerto Rico. Mac intyre et al (1991) reported a handful of algal species collected from Barbados on the basis of two submersible dives.…”
Section: Introductionmentioning
confidence: 99%
“…Mac intyre et al (1991) reported a handful of algal species collected from Barbados on the basis of two submersible dives. Littler et al (1985) reported the deepest known macroalga (to 268 m), an unidentified Corallinales. In a more recent paper based on deployment of a drop camera, Friedlander et al (2014: "Deep Reefs," paragraph 2) reported the presence of crustose coralline algae "from 312 m depth (and probably from 382 m)" at Pitcairn Island (Pacific Ocean), although specimens presumably were not obtained.…”
Section: Introductionmentioning
confidence: 99%
“…This broad taxonomic group is present in virtually every coastal ecosystem, from highly illuminated, intertidal regions to extremely light-limited habitats like rock crevices or depths of 250 m (Johansen, 1981;Littler et al, 1985;Payri et al, 2001;Burdett et al, 2014). The ecological significance of coralline algae varies from playing a fundamental role as ecosystem engineers of highly diverse communities (Foster, 2001;Steller et al, 2003) to being the preferred substrate for settlement of invertebrate larvae (Heyward and Negri, 1999;Williams et al, 2008).…”
Section: Introductionmentioning
confidence: 99%